Between party and movement: conceptual and empirical considerations of the radical right's organizational boundaries and mobilization processes. Issue 4 (8th August 2019) - Minkenberg, Michael
ABSTRACT: The article seeks to contribute to the conceptual and comparative debate with its focus on political parties by approaching the topic through the logic of collective action. Starting from an ideologically centered definition of right-wing radicalism, it conceptualizes the radical right in liberal democracies as a collective actor with different ideological as well as organizational manifestations, the latter most notably in party or movement forms. The article argues that unlike other movement-party linkages, which build on clear typological distinctions between parties and movement, radical right parties almost by definition exhibit movement characteristics in that they continuously engage in 'contentious politics'. Empirical evidence will be drawn from member states of the EU to illustrate the argument. It will be further argued that in the interaction between radical right parties and movements in Western democracies, movements endure where radical right parties remain marginal. In other words, to the extent that radical right parties maintain their movement qualities and become electorally successful, movement mobilization on the far right is inhibited. This 'Western' pattern is contrasted by patterns in Eastern Europe, where more porous borders between radical right parties and movements exist along with symbiotic interactions.